Implications of phyto-feed additives supplementation in buffalo calves on rumen fermentation pattern and microbial population - SONI, P K; AGARWAL, N; KALA, ANJU; AGRAWAL, P; RAHMAN, H; Chaudhary, L C (The Indian Journal of Animal Sciences, 2022)
Natural phyto-feed additives have been identified as a potential rumen fermentation modifier by in vitro studies and by few short-term in vivo trials. However, information on impact on animal performance by their long-term administration is still inadequate. In light of this, the present study was undertaken to examine the rumen fermentation pattern, rumen microbial enzymes and microbial profiles as influenced by long term supplementation of phyto-feed additives to buffalo calves. A six months feeding trial was conducted on 20 male buffaloes (165±4 kg body weight), divided into four groups and fed on diet supplemented with no additive (T0, control), with feed additive FAI @ 1% of dry matter intake (DMI) (T1), with FAII @ 1 ml/kg DMI (T2) and with FAI and FAII switched alternatively after every 15 days (T3). No significant effect was observed on rumen fermentation pattern as well as carboxymethylcellulase, avicelase, xylanase, acetyl esterase, and protease activities in the rumen of buffalo calves. The population density of methanogens, fungi, Ruminococcus flavefaciens, and R. albus decreased significantly in T3 where FAI and FAII were fed alternately, but Fibrobacter succinogenes decreased significantly in T2 where FAII was fed. When compared to the control, the microscopic count of protozoa decreased in all the three supplemented groups. It can be concluded that rumen fermentation, including rumen metabolites and microbial enzymes, were unaffected; however, phyto-feed additives exhibited changes in rumen microbes.